Pengembangan E-LKPD Interaktif Berbasis Project Based Learning Menggunakan Website Wizer.me Materi Kolonialisme dan Perlawanan Bangsa Indonesia di MAN 1 OKU Timur - Arlisa, Rica; Safitri, Sani (Riwayat: Educational Journal of History and Humanities, 2025)
This research is titled "Development of Interactive E-LKPD Based on Project Based Learning Using the Website Wizer.me on Colonialism and Resistance of the Indonesian Nation at MAN 1 OKU Timur." The aim of this research is to develop an interactive E-LKPD based on Project Based Learning using the Wizer.me website that is valid and to improve the effectiveness of the Project Based Learning based E-LKPD using the Wizer.me website covering the topic of colonialism and the resistance of the Indonesian nation at MAN 1 OKU Timur. This research is a type of development research using the Allesi Trollip model. The validity of the E-LKPD is based on the results of expert validation conducted during the beta testing phase through several expert validators, namely content, media, and language. The results of the material validation scored 93, media validation scored 86, and language validation scored 100, all falling into the very valid category. In addition, the effectiveness level of the E-LKPD can be determined from the learning outcomes of the students, which were measured through the field trial stages in the pretest and posttest activities with a score comparison of 30, 41% and an N gain of 0.71, which falls into the high category. Therefore, it can be concluded that the Project Based Learning-Based E-LKPD Using the Wizer.me Website on the Material of Colonialism and the Resistance of the Indonesian Nation at MAN 1 OKU Timur is valid and effective for use in history learning in Class XI.6 of MAN 1 OKU Timur.